Diagnostic delay in moderately/poorly differentiated breast cancer types. Issue 2 (23rd April 2021) - Elfgen, Constanze; Baumgartner, Sabrina; Varga, Zsuzsanna; Reeve, Kelly; Tausch, Christoph J.; Bjelic-Radisic, Vesna; Fleisch, Markus; Güth, Uwe
Abstract : Background: Diagnostic delay of breast cancer related to the false-negative assessment of the healthcare provider leads to tumor progression and might worsen the outcome. Previous studies found some factors associated with provider-related diagnostic delay; however, tumor biology has tended not to be considered. The aim of our study was to find differences in diagnostic delay of poorly differentiated breast cancer types. Methods: Data of 970 patients with newly diagnosed moderately/poorly differentiated (G2/3) breast cancer at the age ≥40 years was retrospectively analyzed regarding breast cancer type, diagnostic delay and its consequence, clinical factors and physician's assessment. Multivariate analysis was used to evaluate associated factors with diagnostic delay. Results: We observed a diagnostic delay in 3.8% ( n = 37) of all patients. Mean delay time was 128 days, and clinically relevant tumor growth was observed in 43.2% of these cases. Delay was significantly higher in the group of triple-negative breast cancer (9.9% versus 2.7, 5.3 and 1.8% in hormonal receptor (HR)+/human epidermal growth factor receptor 2 (HER2)−, HR−/Her2+ and HR+/Her2+, respectively; P value <0.001). Age, breast density and reason for presentation were not correlated to diagnostic delay. Conclusion: Patients with triple-negative breast cancer are at higher risk of receiving a false-negative assessment and experiencing a diagnostic delay. Our results emphasize the importance of a detailed consideration of clinical risk factors and provider training and suggest a broad indication for a core needle biopsy.